Al-Mg-Sc-Zr aluminum-based composite powder and preparation method and application thereof
By adding Co-Cr-Ni medium-entropy alloy powder and erbium oxide powder to the Al-Mg-Sc-Zr-type aluminum-based composite powder, the problem of insufficient tensile strength of Al-Mg-Sc-Zr-type aluminum alloy at high temperatures was solved, and the high-temperature tensile strength was significantly improved, meeting the heat resistance performance requirements of aerospace components.
Patent Information
- Application Number
- CN202210838101.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-17
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-07-17
AI Technical Summary
The Al-Mg-Sc-Zr-based aluminum alloy has insufficient tensile strength at high temperatures and cannot meet the heat resistance requirements of aerospace components.
Using Al-Mg-Sc-Zr-type aluminum-based composite powder, an aluminum-based composite material with high room temperature tensile strength and good high temperature resistance was prepared by adding Co-Cr-Ni medium-entropy alloy powder and erbium oxide powder.
The high-temperature tensile strength of the Al-Mg-Sc-Zr-based aluminum-based composite material is significantly improved, and the tensile strength of 300℃ exceeds 200MPa, meeting the heat resistance performance requirements of aerospace components.
Smart Images

Figure CN115194140B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of laser additive manufacturing, and specifically relates to an Al-Mg-Sc-Zr series aluminum-based composite powder and a preparation method and application thereof. Background Art
[0002] Laser Additive Manufacturing (LAM) technology is a rapid prototyping technology that can produce complex, high-performance, precision aluminum alloy components, which caters to the development trend of lightweight, high-strength, and structural optimization in the manufacturing industry. It is widely needed in the aviation, aerospace, automotive, and shipbuilding industries. Both domestic and foreign countries attach great importance to its development, and companies such as Boeing, Airbus, and General Electric have made key arrangements for the research and promotion of additive manufacturing aluminum alloys.
[0003] At present, the aluminum alloys used for laser additive manufacturing are mainly aluminum-silicon alloys, such as AlSi12, AlSi7Mg, AlSi10Mg, etc.; however, the tensile strength and elongation of laser additively formed parts obtained from these aluminum-silicon alloys are relatively low, which cannot meet the use requirements of high-performance parts.
[0004] In recent years, Al-Mg-Sc- Zr aluminum alloys have attracted much attention in the aviation and aerospace fields. For example, Scalmalloy alloy has a tensile strength of 490MPa and an elongation of 13%. However, the strengthening mechanism of Al-Mg-Sc-Zr aluminum alloys is single, mainly Al3Sc nanoparticle strengthening, which leads to poor high temperature resistance and a tensile strength of less than 200MPa at high temperatures.
[0005] Therefore, how to simultaneously achieve high strength, high toughness and high temperature resistance is an urgent problem to be solved in Al-Mg-Sc-Zr aluminum alloys. Summary of the invention
[0006] The purpose of the present invention is to solve the above-mentioned problems and provide an Al-Mg-Sc-Zr series aluminum-based composite powder and a preparation method and application thereof. The Al-Mg-Sc-Zr series aluminum-based composite material prepared by laser additive forming from the Al-Mg-Sc-Zr series aluminum-based composite powder not only has high room temperature tensile strength, but also has good high temperature resistance. The tensile strength at 300°C can still reach more than 200MPa, meeting the current performance requirements of aerospace heat-resistant aluminum alloy components.
[0007] The technical solution for achieving the purpose of the present invention is: an Al-Mg-Sc-Zr aluminum-based composite powder, which is composed of Al-Mg-Sc-Zr aluminum alloy powder, Co-Cr-Ni medium entropy alloy powder and oxide bait powder.
[0008] Among them, the weight proportion of the erbium oxide powder is 0.1-1.0%, the weight proportion of the Co-Cr-Ni medium entropy alloy powder is 1.0-5.0%, and the rest is the Al-Mg-Sc-Zr aluminum alloy powder.
[0009] In the Co-Cr-Ni medium entropy alloy powder, Co, Cr and Ni are in an equimolar ratio.
[0010] The Al-Mg-Sc-Zr aluminum alloy powder includes the following components and their weight percentages: 1.0-5.0% Mg, 0.3-1.0% Sc, 0.05-0.35% Zr, 0.05-0.5% Mn, 0.1-0.2% Si, 0.01-0.03% Mo, and the rest Al.
[0011] The preparation method of the Al-Mg-Sc-Zr series aluminum-based composite powder is to uniformly mix the Al-Mg-Sc-Zr series aluminum alloy powder, the Co-Cr-Ni medium entropy alloy powder and the erbium oxide powder, dry them, and sieve them to obtain the Al-Mg-Sc-Zr series aluminum-based composite powder.
[0012] The preparation method of the Al-Mg-Sc-Zr aluminum alloy powder comprises the following steps:
[0013] S11: adding each component according to weight percentage into a vacuum melting furnace for vacuum melting.
[0014] S12: Atomizing the metal droplets with an inert gas.
[0015] S13: Drying, and passing through a 150-250 mesh sieve to obtain Al-Mg-Sc-Zr aluminum alloy powder.
[0016] In the above step S11, the temperature in the vacuum melting furnace is 600-800° C., and the pressure in the vacuum melting furnace is 0.5-0.6 MPa.
[0017] In the above step S12, the temperature of the atomization treatment is 600-800° C., the pressure is 5-8.5 MPa, and the time is 0.5-1.5 h.
[0018] The preparation method of the Co-Cr-Ni medium entropy alloy powder comprises the following steps:
[0019] S21: adding each component into a vacuum melting furnace in an equimolar ratio for vacuum melting.
[0020] S22: Atomizing the metal droplets using an inert gas.
[0021] S23: drying, and passing through a 150-250 mesh sieve to obtain a Co-Cr-Ni medium entropy alloy powder.
[0022] In the above step S21, the temperature in the vacuum melting furnace is 1000-1200° C., and the pressure in the vacuum melting furnace is 0.5-0.6 MPa.
[0023] In the above step S22, the temperature of the atomization treatment is 1000-1200°C, the pressure is 5-8.5 MPa, and the time is 0.5-1.5 h.
[0024] The erbium oxide powder is preferably an erbium oxide powder modified with an alkyl sulfonate.
[0025] The method of modifying the alkyl sulfonate is as follows:
[0026] S31: Disperse erbium oxide powder in aqueous solution and ultrasonically oscillate for 0.1 to 1 h.
[0027] S32: Add alkyl sulfonate surfactant under high-speed stirring and stir for 18 to 30 hours.
[0028] S33: centrifugal separation, washing, drying at 80-100°C for 16-20h, and finally passing through a 150-250 mesh sieve.
[0029] The above-mentioned Al-Mg-Sc-Zr series aluminum-based composite powder is used in the preparation of Al-Mg-Sc-Zr series aluminum-based composite materials by laser additive forming.
[0030] The laser additive manufacturing includes laser additive manufacturing and heat treatment.
[0031] The laser additive process parameters are as follows: laser power is 200-400 W, scanning speed is 500-1200 mm / s, scanning spacing is 0.04-0.14 mm, scanning layer thickness is 0.03-0.07 mm, and the rotation angle between adjacent layers is 67°.
[0032] The heat treatment process parameters are as follows: temperature is 250-325° C., heating rate is 50° C. / min, and holding time is 2-6 hours.
[0033] The present invention has the positive effects:
[0034] (1) The Al-Mg-Sc-Zr aluminum-based composite powder of the present invention can significantly improve the high temperature resistance of the Al-Mg-Sc-Zr aluminum-based composite material by adding Co-Cr-Ni medium entropy alloy powder and oxide bait powder. The tensile strength at 250°C exceeds 300MPa, and the tensile strength at 300°C exceeds 200MPa, which is significantly higher than the high temperature mechanical properties of the existing laser additive aluminum alloy powder and meets the current performance requirements of aerospace heat-resistant aluminum alloy parts.
[0035] (2) The Co-Cr-Ni medium entropy alloy powder in the Al-Mg-Sc-Zr aluminum-based composite powder of the present invention has a low equilibrium solid solubility and a small diffusion coefficient, and can generate precipitated particles in the alloy, and the coarsening rate of the particles is slow. With the help of the rapid cooling characteristics of additive manufacturing, it can promote the generation of uniformly dispersed fine precipitate phases, produce precipitation strengthening, and thus improve the high temperature strength of the aluminum-based composite material.
[0036] (3) The erbium oxide powder in the Al-Mg-Sc-Zr aluminum-based composite powder of the present invention reacts with aluminum to form Al3Er, which, as a fine second phase, pins dislocations in the alloy matrix, hindering dislocation movement; and pins them at the grain boundaries, hindering grain boundary migration and grain growth, thereby avoiding the problem of fracture of the aluminum-based composite material while improving its strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the SEM image of the Al-Mg-Sc-Zr aluminum-based composite powder prepared in Example 1.
[0038] Figure 2 The metallographic diagrams of the Al-Mg-Sc-Zr aluminum-based composite materials obtained in Application Examples 1 to 4; wherein: Application Example 1 corresponds to Figure 2 i. Application Example 2 Figure 2 h、Application Example 3 Figure 2 j. Application Example 4 Figure 2 g.
[0039] Figure 3 This is a tensile engineering stress-strain curve of the Al-Mg-Sc-Zr aluminum-based composite material prepared in Application Example 1 at a temperature of 25 to 400°C. DETAILED DESCRIPTION
[0040] (Example 1)
[0041] The Al-Mg-Sc-Zr aluminum-based composite powder of this embodiment is composed of Al-Mg-Sc-Zr aluminum alloy powder, Co-Cr-Ni medium entropy alloy powder and bait oxide powder.
[0042] Among them, the weight proportion of erbium oxide powder is 0.5%, the weight proportion of Co-Cr-Ni medium entropy alloy powder is 3.0%, and the rest is Al-Mg-Sc-Zr aluminum alloy powder.
[0043] In the Co-Cr-Ni medium entropy alloy powder, Co, Cr and Ni are in an equal molar ratio.
[0044] In the Al-Mg-Sc-Zr aluminum alloy powder, the components and their weight percentages are as follows: 4.0% Mg, 0.8% Sc, 0.25% Zr, 0.3% Mn, 0.15% Si, 0.02% Mo, and the rest is Al.
[0045] The preparation method of the Al-Mg-Sc-Zr aluminum-based composite powder of this embodiment comprises the following steps:
[0046] S1: Prepare Al-Mg-Sc-Zr aluminum alloy powder.
[0047] S11: adding each component according to weight percentage into a vacuum melting furnace for vacuum melting.
[0048] Among them, the temperature in the vacuum melting furnace is 700±5℃, and the pressure in the vacuum melting furnace is 0.5~0.6MPa.
[0049] S12: using argon gas to atomize the metal droplets.
[0050] The atomization treatment temperature is 700±5°C, the pressure is 7.0±0.1MPa, and the time is 1h.
[0051] S13: Drying, passing through a 200-mesh sieve, and obtaining Al-Mg-Sc-Zr aluminum alloy powder with an average particle size of 75 μm.
[0052] S2: Preparation of Co-Cr-Ni medium entropy alloy powder.
[0053] S21: adding each component into a vacuum melting furnace in an equimolar ratio for vacuum melting.
[0054] Among them, the temperature in the vacuum melting furnace is 1100±5℃, and the pressure in the vacuum melting furnace is 0.5~0.6MPa.
[0055] S22: using argon gas to atomize the metal droplets.
[0056] Among them, the atomization treatment temperature is 1100±5℃, the pressure is 8.0±0.1MPa, and the time is 1h.
[0057] S23: drying, and passing through a 200-mesh sieve to obtain a Co—Cr—Ni medium entropy alloy powder with an average particle size of 75 μm.
[0058] S3: preparing modified erbium oxide powder.
[0059] S31: Disperse erbium oxide powder in aqueous solution and ultrasonically oscillate for 0.5 h.
[0060] S32: Add an equal weight of sodium alkyl sulfonate (and erbium oxide) under high-speed stirring and stir for 24 hours.
[0061] S33: centrifugation, washing with distilled water for multiple times to remove unadsorbed sodium alkyl sulfonate, then drying in a vacuum drying oven at 100° C. for 18 hours, and finally passing through a 200-mesh sieve to obtain a modified erbium oxide powder with an average particle size of 75 μm.
[0062] S4: The Al-Mg-Sc-Zr aluminum alloy powder obtained in step S1, the Co-Cr-Ni medium entropy alloy powder obtained in step S2, and the erbium oxide powder obtained in step S3 are placed in a large powder mixing device and mixed for 6 hours, then dried, and finally sieved through a 200-mesh sieve to obtain an Al-Mg-Sc-Zr aluminum-based composite powder with an average particle size of 75 μm.
[0063] The SEM image of the Al-Mg-Sc-Zr aluminum-based composite powder prepared in this embodiment is shown in Figure 1 ,Depend on Figure 1 It can be seen that the Al-Mg-Sc-Zr aluminum-based composite powder prepared in this embodiment is spherical.
[0064] (Application example 1)
[0065] The Al-Mg-Sc-Zr aluminum-based composite material is prepared by laser additive forming using the Al-Mg-Sc-Zr aluminum-based composite powder of Example 1, and the specific method is as follows:
[0066] The substrate is heated to a temperature of 150°C, and then the Al-Mg-Sc-Zr aluminum-based composite powder is added to the substrate through a laser additive process, followed by heat treatment to obtain the Al-Mg-Sc-Zr aluminum-based composite material.
[0067] Among them, the laser additive process parameters are as follows: laser power is 300W, scanning speed is 1000mm / s, scanning spacing is 0.1mm, scanning layer thickness is 0.05mm, and the rotation angle between adjacent layers is 67°.
[0068] The heat treatment process parameters are as follows: temperature is 300±5℃, heating rate is 50℃ / min, and holding time is 4h.
[0069] The metallographic image of the Al-Mg-Sc-Zr aluminum matrix composite material prepared in this application example is shown in Figure 2 i, by Figure 2 It can be seen that the Al-Mg-Sc-Zr aluminum-based composite material has an extremely high density and is free of cracks and defects.
[0070] (Test Example 1)
[0071] The Al-Mg-Sc-Zr aluminum matrix composite material prepared in Example 1 was subjected to room temperature (25°C) tensile test and high temperature tensile test. The engineering stress-strain curves are shown in Figure 3 .
[0072] Depend on Figure 3 It can be seen that the Al-Mg-Sc-Zr aluminum-based composite material prepared in Application Example 1 has a room temperature (25°C) tensile strength of 489 MPa, a 250°C tensile strength of more than 300 MPa, and a 300°C tensile strength of more than 200 MPa, which are significantly higher than the high-temperature mechanical properties of existing laser additive aluminum alloy powders and meet the current performance requirements of aerospace heat-resistant aluminum alloy components.
[0073] (Example 2 to Example 4)
[0074] The preparation method of the Al-Mg-Sc-Zr aluminum-based composite powder in each embodiment is the same as that in Example 1, except that the weight percentage of each powder and the weight percentage of each component in the Al-Mg-Sc-Zr aluminum alloy powder are specifically shown in Table 1.
[0075] Table 1
[0076] Example 1 Example 2 Example 3 Example 4 Oxidized bait powder weight percentage 0.5wt% 0.4wt% 0.3wt% 0.2wt% Weight proportion of Co-Cr-Ni medium entropy alloy powder 3.0wt% 2.5wt% 2.0wt% 1.5wt% Mg 4.0wt% 3.5wt% 3.5wt% 3.0wt% Sc 0.8wt% 0.8wt% 0.5wt% 0.5wt% Zr 0.25wt% 0.25wt% 0.1wt% 0.1wt% Mn 0.3wt% 0.2wt% 0.2wt% 0.1wt% Si 0.15wt% 0.15wt% 0.15wt% 0.15wt% Mo 0.02wt% 0.02wt% 0.02wt% 0.02wt%
[0077] (Application Example 2 to Application Example 4)
[0078] The Al-Mg-Sc-Zr aluminum-based composite materials were prepared by using the Al-Mg-Sc-Zr aluminum-based composite powders of Examples 2 to 4 respectively and referring to the laser additive forming method of Application Example 1.
[0079] The metallographic diagram of the Al-Mg-Sc-Zr aluminum matrix composite material prepared in Application Example 2 is shown in Figure 2 h, by Figure 2 hIt can be seen that the Al-Mg-Sc-Zr aluminum-based composite material has a high density, no cracks and very few defects.
[0080] The metallographic diagram of the Al-Mg-Sc-Zr aluminum matrix composite material prepared in Application Example 3 is shown in Figure 2 j, by Figure 2 jIt can be seen that the Al-Mg-Sc-Zr aluminum-based composite material has a general density, but no cracks and a few defects.
[0081] The metallographic diagram of the Al-Mg-Sc-Zr aluminum matrix composite material prepared in Application Example 4 is shown in Figure 2 g, by Figure 2 g It can be seen that the Al-Mg-Sc-Zr aluminum-based composite material has a general density, but no cracks and a few defects.
[0082] (Test Example 2 to Test Example 4)
[0083] The Al-Mg-Sc-Zr aluminum-based composite materials prepared in each application example were subjected to room temperature (25°C) tensile tests and high temperature (250°C) tensile tests. The results are shown in Table 2.
[0084] Table 2
[0085] Application Example 1 Application Example 2 Application Example 3 Application Example 4 Comparative application example 1 Comparative Application Example 2 Tensile strength at 25℃ 489MPa 461MPa 427MPa 412MPa 405MPa / 250℃ tensile strength 326MPa 295MPa 267MPa 252MPa 110MPa / Porosity 0.24% 0.46% 0.79% 0.89% 1.21% 1.03% Average microhardness 205HV 186HV 153HV 128HV 100HV 112HV
[0086] (Test example)
[0087] The relevant properties of the Al-Mg-Sc-Zr aluminum-based composite materials prepared in each application example were tested, and the results are still shown in Table 2.
[0088] (Comparative Example 1)
[0089] The Al-Mg-Sc-Zr aluminum-based composite powder in this comparative example is different from that in Example 1 in that it does not contain Co-Cr-Ni medium-entropy alloy powder [that is, the weight proportion of erbium oxide powder is still 0.5%, and the rest is Al-Mg-Sc-Zr aluminum alloy powder].
[0090] The method for preparing the Al-Mg-Sc-Zr aluminum-based composite powder in this comparative example is different from that in Example 1 in that step S2 is not included.
[0091] (Comparative Application Example 1)
[0092] The Al-Mg-Sc-Zr aluminum-based composite material was prepared by using the Al-Mg-Sc-Zr aluminum-based composite powder of Comparative Example 1 and referring to the laser additive forming method of Application Example 1.
[0093] The relevant properties of the aluminum-based composite material were tested, and the results are still shown in Table 2.
[0094] The aluminum-based composite material was subjected to room temperature (25°C) tensile test and high temperature (250°C) tensile test, and the results are still shown in Table 2.
[0095] (Comparative Example 2)
[0096] The Al-Mg-Sc-Zr aluminum-based composite powder of this comparative example is different from that of Example 1 in that it does not contain erbium oxide powder [that is, the weight proportion of the entropy alloy powder in Co-Cr-Ni is still 3.0%, and the rest is Al-Mg-Sc-Zr aluminum alloy powder].
[0097] The method for preparing the Al-Mg-Sc-Zr aluminum-based composite powder in this comparative example is different from that in Example 1 in that step S3 is not included.
[0098] (Comparative Application Example 2)
[0099] The Al-Mg-Sc-Zr aluminum-based composite material was prepared by using the Al-Mg-Sc-Zr aluminum-based composite powder of Comparative Example 2 and referring to the laser additive forming method of Application Example 1.
[0100] The relevant properties of the aluminum-based composite material were tested, and the results are still shown in Table 2.
[0101] The aluminum-based composite material was subjected to a room temperature tensile test, and the result showed that brittle fracture occurred on the material cross section.
Claims
1. An Al-Mg-Sc-Zr aluminum-based composite powder, characterized in that: It is composed of Al-Mg-Sc-Zr aluminum alloy powder, Co-Cr-Ni medium entropy alloy powder and oxide bait powder; The weight proportion of the erbium oxide powder is 0.1-1.0%, the weight proportion of the Co-Cr-Ni medium entropy alloy powder is 1.0-5.0%, and the rest is the Al-Mg-Sc-Zr aluminum alloy powder.
2. The Al-Mg-Sc-Zr aluminum-based composite powder according to claim 1, characterized in that: In the Co-Cr-Ni medium entropy alloy powder, Co, Cr and Ni are in an equimolar ratio.
3. The Al-Mg-Sc-Zr aluminum-based composite powder according to claim 1, characterized in that: The Al-Mg-Sc-Zr aluminum alloy powder includes the following components and their weight percentages: 1.0-5.0% Mg, 0.3-1.0% Sc, 0.05-0.35% Zr, 0.05-0.5% Mn, 0.1-0.2% Si, 0.01-0.03% Mo, and the rest Al.
4. A method for preparing the Al-Mg-Sc-Zr aluminum-based composite powder according to claim 1, characterized in that: The Al-Mg-Sc-Zr aluminum alloy powder, the Co-Cr-Ni medium entropy alloy powder and the erbium oxide powder are uniformly mixed, dried and sieved to obtain the powder.
5. The method for preparing the Al-Mg-Sc-Zr aluminum-based composite powder according to claim 4, characterized in that: The preparation method of the Al-Mg-Sc-Zr aluminum alloy powder comprises the following steps: S11: adding each component according to weight percentage into a vacuum melting furnace for vacuum melting; S12: atomizing the metal droplets using an inert gas; S13: drying, and passing through a 150-250 mesh sieve to obtain Al-Mg-Sc-Zr aluminum alloy powder; In the above step S11, the temperature in the vacuum melting furnace is 600-800° C., and the pressure in the vacuum melting furnace is 0.5-0.6 MPa; In the above step S12, the temperature of the atomization treatment is 600-800° C., the pressure is 5-8.5 MPa, and the time is 0.5-1.5 h.
6. The method for preparing the Al-Mg-Sc-Zr aluminum-based composite powder according to claim 4, characterized in that: The preparation method of the Co-Cr-Ni medium entropy alloy powder comprises the following steps: S21: adding each component into a vacuum melting furnace in an equal molar ratio to perform vacuum melting; S22: atomizing the metal droplets using an inert gas; S23: drying, and passing through a 150-250 mesh sieve to obtain a Co-Cr-Ni medium entropy alloy powder; In the above step S21, the temperature in the vacuum melting furnace is 1000-1200° C., and the pressure in the vacuum melting furnace is 0.5-0.6 MPa; In the above step S22, the temperature of the atomization treatment is 1000-1200°C, the pressure is 5-8.5 MPa, and the time is 0.5-1.5 h.
7. The method for preparing the Al-Mg-Sc-Zr aluminum-based composite powder according to claim 4, characterized in that: The erbium oxide powder is an erbium oxide powder modified by an alkyl sulfonate; the method of modifying the alkyl sulfonate is as follows: S31: dispersing erbium oxide powder in aqueous solution and ultrasonically oscillating for 0.1 to 1 h; S32: adding an alkyl sulfonate surfactant under high-speed stirring and stirring for 18 to 30 hours; S33: centrifugal separation, washing, drying at 80-100°C for 16-20h, and finally passing through a 150-250 mesh sieve.
8. Use of the Al-Mg-Sc-Zr aluminum-based composite powder according to claim 1 in preparing Al-Mg-Sc-Zr aluminum-based composite materials by laser additive forming.
9. The use according to claim 8, characterized in that: The laser additive forming includes laser additive and heat treatment; The laser additive process parameters are as follows: laser power is 200-400W, scanning speed is 500-1200mm / s, scanning spacing is 0.04-0.14mm, scanning layer thickness is 0.03-0.07mm, and the rotation angle between adjacent layers is 67°; The heat treatment process parameters are as follows: temperature is 250-325° C., heating rate is 50° C. / min, and holding time is 2-6 hours.
Citation Information
Patent Citations
Special high strength 7-series aluminum-based composite material for 3D printing and preparation method thereof
CN111842890A
CrCoNi medium-entropy alloy reinforced Al-based composite material and preparation method thereof
CN113957294A